Spatial Analysis of Kermanshah province Regional Development by using multi-criteria decision-making models - Hossein nzmfar; Ameneh alibakhshi; Soheyla bakhtar (تحقیقات کاربردی علوم جغرافیایی)
With the aim of development and reducing regional inequalities, regional planning is one of the most important subiects in developing countries. Regional planning requires the identification of the position of areas relative to each other in terms of their development. The aim of this study is to investigate and assess the level of Kermanshah province in terms of development indicators in order to find out the level of regional inequalities. The population of Kermanshah province is considered as statistical population. According to the investigated parameters of the research approach, it is “Descriptive - quantitative and analytical". This research is trying to use the 61 indicators based on 1390 almanac statistics and utilizes three statistical techniques of Vikor, Electre, SAW and integration of  results with Copeland  technique, classify existing inequalities in Kermanshah province. The results show that the Levels of development has been unbalanced and there is large gap and inequality among different cities of province in terms of development. The difference and inequality exist in various sectors of infrastructure such as economic, health, education, culture, social welfare and social. Only one city Gilangharb is developed and the rest of cities are semi- developed and deprived. To reduce inequalities in development in the province it is suggested that distribution of health, education and infrastructure indicators should be directed towards balanced growth and the index of infrastructure be emphasized more than the other indicators.